Prevalence of mental disorders in a population requesting health services at a primary health care center and its association with suicidal ideation and perceived disability - Mérida R. Rodríguez; Hernán G. Rincón H; Margarita M. Velasco P; Carlos A. Hernández A; Martha L. Ramos; José A. González (Universidad de Antioquia, 2012)
Objective: this study's goal was to determine the most prevalent mental disorders and the impact on the perception of disability and suicidal ideation among the population from a primary health care center in the city of Cali. Methodology: a cross sectional study was conducted on 254 patients who were screened with the prime-md instrument. Descriptive statistics was used in the analysis to determine the most frequent disorders. Similarly, a multiple analysis with logistic and Poisson regressions using robust variance was conducted to determine the influence of mental disorders on disability and suicidal ideation. Results: most patients were female, young, and mature adults. Depression was present in 66.8% of all cases, followed by somatization disorder and anxiety. Half of the patients had had suicidal ideations at some point in their lives, and three out of four patients claimed to suffer from some kind of disability. Upon adjusting for the covariables, depression and anxiety disorders had a strong association with suicidal ideation and perceived disability that was overestimated by the logistic regression. Conclusion: depression and anxiety were the most common disorders and showed a strong association with suicidal ideation and disability. This is why it is necessary to screen for those disorders among adults using primary health care services. Likewise, we suggest considering Poisson regression with robust variance in cross-sectional studies in health services.